2013
DOI: 10.1128/jmbe.v14i1.492
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Impact of the Kansas IDeA Network of Biomedical Research Excellence Program on Undergraduate Participation in Research

Abstract: The Kansas IDeA Network of Biomedical Research Excellence (K-INBRE) was established in 2001 and is a network of 10 higher-education institutions in Kansas and northern Oklahoma. The program is funded by the Institutional Development Award (IDeA) program of the National Institutes of Health (NIH). As part of the program’s goal to enhance the research infrastructure in Kansas, a training program was developed to encourage undergraduates to participate in biomedical research. From September 2002 to May 2012, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 7 publications
2
15
0
Order By: Relevance
“…Almost 80% of our respondents indicated that their participation in the K-INBRE symposium helped them in their appreciation of the value of research. This is consistent with other program surveys that assessed the impact of undergraduate research experiences (3, 5-7) and with our laboratory's previous assessments of the K-INBRE program (1).…”
Section: Symposium Formatsupporting
confidence: 91%
See 2 more Smart Citations
“…Almost 80% of our respondents indicated that their participation in the K-INBRE symposium helped them in their appreciation of the value of research. This is consistent with other program surveys that assessed the impact of undergraduate research experiences (3, 5-7) and with our laboratory's previous assessments of the K-INBRE program (1).…”
Section: Symposium Formatsupporting
confidence: 91%
“…The Kansas INBRE, or K-INBRE, is a product of that 2001 initiative. The University of Kansas Medical Center (KUMC), a comprehensive medical and biomedical PhD-granting graduate school, serves as the administrative center of the program (1). The network also includes two comprehensive universities, the University of Kansas-Lawrence and Kansas State University, with under-graduate and graduate PhD-level degrees in biomedical sciences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to OK-INBRE participants who completed undergraduate degrees in Oklahoma, where 80% of them are pursing or have completed a graduate degree (MS or PhD) in the sciences, 20% are pursing or have completed a MD/DO degree, and another 19% are enrolled in or have completed a health sciences–related degree, 21%, 34%, and 22% of research program graduates in North Dakota are pursing or have completed a PhD degree, are pursing or have completed a MD/DO degree, and are enrolled in or have completed a health sciences-related degree, respectively (25). In Kansas, 37% of research program graduates are pursing or have completed a PhD degree, 19% are pursing or have completed a MD/DO degree, and 12% are enrolled or have completed a health sciences–related degree (26). It is worth noting that North Dakota and Kansas programs were only able to report descriptive statistics on degree enrollment and completion outcomes, while the Oklahoma program was able to apply statistical analyses to determine whether these differences across categories were significant (25, 26).…”
Section: Discussionmentioning
confidence: 99%
“…In Kansas, 37% of research program graduates are pursing or have completed a PhD degree, 19% are pursing or have completed a MD/DO degree, and 12% are enrolled or have completed a health sciences–related degree (26). It is worth noting that North Dakota and Kansas programs were only able to report descriptive statistics on degree enrollment and completion outcomes, while the Oklahoma program was able to apply statistical analyses to determine whether these differences across categories were significant (25, 26). The OK-INBRE findings are also consistent with prior publications indicating that experiences in a research program can improve participation and persistence, often by strengthening students’ views of themselves as scientists (23).…”
Section: Discussionmentioning
confidence: 99%